2017
DOI: 10.1002/adom.201600989
|View full text |Cite
|
Sign up to set email alerts
|

Colorless‐to‐Black/Gray Electrochromic Devices Based on Single 1‐Alkyl‐1′‐Aryl Asymmetric Viologen‐Modified Monolayered Electrodes

Abstract: In the rising tendency of electrochromics and incipient development of multicolor systems, big attention is recently being paid to the colorless‐to‐black or gray electrochromic (EC) materials, since they can extend the applicability of the EC technology. However, the achievement of high performance EC materials which intrinsically provide colorless‐to‐gray/black electrochromism remains a strategic challenge. The present study reports on colorless‐to‐black/gray EC devices (ECDs) based on new 1‐alkyl‐1′‐aryl asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…The LCD utilizing dye‐doped cholesteric LC (chLC) and electrowetting devices have excellent optical properties and fast response time but too high driving voltage limits the application to portable devices like OST‐HMD . On the other hand, reported ECDs using various electrochromic materials have very low driving voltage suitable for the portable devices . Among reported electrochromic materials, fluoran dye exhibits superior characteristics than viologen and polymer materials in all evaluation items.…”
Section: Resultsmentioning
confidence: 99%
“…The LCD utilizing dye‐doped cholesteric LC (chLC) and electrowetting devices have excellent optical properties and fast response time but too high driving voltage limits the application to portable devices like OST‐HMD . On the other hand, reported ECDs using various electrochromic materials have very low driving voltage suitable for the portable devices . Among reported electrochromic materials, fluoran dye exhibits superior characteristics than viologen and polymer materials in all evaluation items.…”
Section: Resultsmentioning
confidence: 99%
“…Those include: transition metal oxides, prussian blue systems, viologens, conjugated polymers, transition metal complexes and metal phthalocyanines [ 9 , 10 ]. Of those, transition metal oxides, viologens and conjugated polymers have been reported to exhibit bleached and dark coloured states [ 6 , 11 , 12 ]. Each of those systems has its strong and weak points, therefore, each may excel when presented with different requirements.…”
Section: Concepts and Considerationsmentioning
confidence: 99%
“…Alesanco et al [ 11 ] report another approach to the use of viologen derivatives as electrochromic systems ( Scheme 1 ). In this case, the Authors focused on asymmetric derivatives, equipped with terminal phosphate groups to promote adherence to the TiO 2 monolayer, which the authors deposited on the working electrode of their devices.…”
Section: Pursuing the Goalmentioning
confidence: 99%
“…Another clear example of using gel electrolytes to modulate the equilibrium of the radical cation monomer and dimer is from recent work based on 1-alkyl-1′-aryl substituted asymmetric viologens ( Figure 9 aI and bI) [ 155 ]. The latter, with electrochromic and electrochemical behavior about midway between the corresponding symmetric viologens, have been demonstrated to provide neutral tones (i.e., gray, blackish) [ 156 ] when conveniently tested in a water-based gel-type electrolyte ( Figure 9 aII and bII). This report confirmed that using these asymmetric viologens (i.e., 1-ethyl-1′-( p -cyanophenyl)-4,4′-bipyridinium dibromide (et-pCNVio, Figure 9 aI) and 1-benzyl-1′-( p -cyanophenyl)-4,4′-bipyridinium dibromide (Bn-pCNVio, Figure 9 bI) in a PVA-borax gel-type electrolyte led to different colored states, and therefore different absorption profiles, from the ones registered for anhydrous liquid systems.…”
Section: Stabilization Of Species In All-in-one Gel-based Ecdsmentioning
confidence: 99%